THE NECESSITY OF IMPROVING CULTURAL AWARENESS OF EFL LEARNERS IN STMIK HANDAYANI MAKASSAR - Yuliah Abdul Haris (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
This paper mainly discusses the relationship between language and culture. Language and culture are closely related. If one does not understand the cultural backgrounds, he or she cannot learn the target language really well because any language is an integral part of its culture. Moreover, misunderstanding between the speaker whose first language is English and the speaker whose first language is not English occur between them.  The writer believes that there is still an important cultural element missing from foreign language education in Indonesian EFL classes in such as in STMIK Handayani Makassar. Therefore, English learning in STMIK Handayani Makassar should not only to learn the language, but also to learn its culture. To improve students’ sensitivity for cultural difference between the West and the East and to raise their cultural awareness, English teachers at schools are required not only to teach language but also to impart cultural background knowledge and further to deal with the relationship between language and culture well. This article starts with the necessity of teaching cultural awareness in English teaching at schools, and then this paper discusses some common cultural language mistakes by English Foreign Language learners in STMIK Handayani Makassar.